PENGGUNAAN METODE PEMBELAJARAN TREFFINGER UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA DALAM MATA PELAJARAN MEKANIKA TEKNIK - Mukti, Wulan Tresna (2014)
Student grades are still below KKM (Minimal Completeness Criteria), a low learning motivation and learning difficulties in students create appropriate learning method is needed. Learning Method Treffinger yet widely used in research and in teaching and learning activities. This research was conducted in order to determine student achievement before and after using Treffinger learning methods in engineering mechanics subjects as well as to know the difference. The population in this study is a class X student of SMK Architecture Engineering, amounting to 72 students. While the sample used is a class X student of SMK TGB 1, amounting to 24 students. The method used in this study is an experimental method (Pre-Experimental Designs) to form One-Group Pretest-posttest design. In this form, a group treated with Treffinger learning methods. Where researchers provide pretest prior to treatment, and provide post-test after treatment. Analysis of the data used in this study is a qualitative and quantitative analysis. Based on the analysis of the data has been obtained, after the implementation of learning methods Treffinger there is an increase in cognitive learning achievement of students by 46% while the increase in affective learning achievement of students by 52%. This means that students can follow the course with a good as well as the achievements of the students fairly well. With the implementation of this method in engineering mechanics subjects, students can achieve KKM and understand the assigned material so it does not run into trouble learning. Perolehan nilai siswa yang masih di bawah KKM (Kriteria Ketuntasan Minimal), motivasi belajar yang rendah serta kesulitan belajar pada siswa membuat metode pembelajaran yang tepat sangat dibutuhkan. Metode Pembelajaran Treffinger belum banyak digunakan dalam penelitian maupun dalam kegiatan belajar mengajar. Penelitian ini dilaksanakan dengan tujuan untuk mengetahui prestasi belajar siswa sebelum dan setelah menggunakan metode pembelajaran Treffinger dalam mata pelajaran mekanika teknik serta untuk mengetahui perbedaannya. Populasi dalam penelitian ini adalah siswa kelas X SMK Teknik Gambar Bangunan yang berjumlah 72 siswa. Sedangkan sample yang digunakan adalah siswa SMK kelas X TGB 1 yang berjumlah 24 siswa. Metode yang digunakan dalam penelitian ini adalah metode eksperimen (Pre-Experimental Designs) dengan bentuk One-Group Pretest-Postest Design. Pada bentuk ini, suatu kelompok diberi perlakuan dengan metode pembelajaran treffinger. Dimana peneliti memberikan Pretes sebelum melakukan treatment, dan memberikan postes setelah melakukan treatment. Analisis data yang digunakan dalam penelitian ini adalah analisis kualitatif dan kuantitatif. Berdasarkan analisis dari data yang telah didapat, setelah diterapkannya metode pembelajaran treffinger terdapat peningkatan prestasi belajar kognitif siswa sebesar 46% sedangkan peningkatan prestasi belajar afektif siswa sebesar 52%. Ini berarti siswa dapat mengikuti pelajaran dengan baik serta prestasi yang dicapai siswa terbilang baik. Dengan diterapkannya metode ini dalam mata pelajaran mekanika teknik, siswa dapat mencapai KKM serta memahami materi yang diberikan sehingga tidak mengalami lagi kesulitan belajar.